Hubungan Peran Orang Tua dengan Kemampuan Sosialisasi Anak Usia Prasekolah - Evita Meriana; Fiki Wijayanti (Jurnal Informatika dan Kesehatan, 2025)
Preschool children have the ability to move actively because their physical and motor development is getting better. During this period, significant biological, psychological, cognitive growth and development and socialization abilities occur.  Socialization ability is a child's ability to adapt to the wider social world. One of the factors that influences the socialization abilities of preschool children is the role of parents. Meanwhile, the impact of the lack of parental role is that children become egoistic and individualistic. The purpose of this research to determine the relationship between the role of parents and the socialization abilities of preschool children. This research usesCorrelational analyticswith approachcross sectional. The population of this research was 128 respondents. The sample in this research was 97 respondents. Sampling techniquepropotionate random sampling, data collection tools using questionnaires. Test analysis using testskendall’s tau-b with p < α 0.05. The research results showed that the role of parents was in the good category as many as 66 people (68.0%). Most children's socialization abilities are in the sufficient category, namely 51 people (52.6%). Obtaining a p value = 0.000 < 0.05, it can be concluded that there is a relationship between the role of parents and the socialization abilities of preschool children. . The correlation coefficient value for socialization ability is 0.356, so it can be concluded that the relationship between the socialization ability variables is quite strong at a significance of 0.05, and the two variables have a positive relationship. There is a relationship between the role of parents and the socialization abilities of preschool children. It is hoped that parents can maintain stimulation, especially in the socialization aspect, to optimize children's socialization abilities.   ABSTRAK Anak prasekolah mempunyai kemampuan untuk bergerak aktif karena perkembangan fisik – motoriknya sudah semakin baik. Pada masa ini, terjadi pertumbuhan dan perkembangan biologis, psikologis, kognitif, dan kemampuan sosialisasi yang begitu signifikan.  Kemampuan sosialisasi merupakan kemampuan anak dalam beradaptasi dengan dunia sosial yang lebih luas. Salah satu faktor yang mempengaruhi kemampuan sosialisasi anak usia prasekolah adalah peran orang tua. Sementara itu, dampak dari kurangnya peran orang tua adalah anak-anak menjadi egoisme dan individualisme. Tujuan dari penelitian ini untuk mengetahui hubungan peran orang tua dengan kemampuan sosialisasi anak usia prasekolah. Penelitian ini menggunakan  Analitik korelasional dengan pendekatan cross sectional. Populasi peneltian ini adalah 128 responden. Sampel dalam peneltian ini 97 responden Teknik pengambilan sampel propotionate random sampling, alat pengumpulan data menggunakan kuesioner Uji analisis menggunakan uji kendall’s tau-b dengan p < α 0,05 Hasil penelitian menunjukkan peran orang tua dalam kategori baik sebanyak 66 orang (68,0%). Kemampuan sosialisasi anak paling banyak pada kategori cukup  yaitu 51 orang (52,6%). Diperoleh nilai p value = 0,000 < 0,05 maka dapat disimpulkan bahwa ada hubungan antara peran orang tua dengan kemampuan sosialisasi anak usia prasekolah. . Nilai koefisiensi korelasi kemampuan sosialisasi sebesar 0,356 maka dapat disimpulkan bahwa hubungan anatara variable kemampuan sosialisasi cukup kuat pada signifikansi 0,05, dan kedua variable memiliki hubungan yang positif. Ada hubungan peran orang tua dengan kemampuan sosialisasi anak usia prasekolah. Diharapkan orang tua dapat mempertahankan stimulasi terutama pada aspek sosialisasi untuk mengoptimalkan kemampuan sosialisasi anak.